Catalogue of collections - Holmes, William H. (Washington : Government Printing Office, 1926)
Contiene: alphabetical list of permanent accessions with page references to catalogue, list of artists with page references to catalogue, catalogue of permanent accessions, with bigraphies of artists, list of loans